Learner Variables in Language Learning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
There are many cognitive factors that affect language learning. Among the cognitive factors, there is memory, attention and awareness, forgetting, context or environment. In which the learning process takes place. Memory plays a part in bringing about a higher and lower level of language mastery.